Peroneus Brevis flap in Achilles tendon reconstruction. Clinical, radiological and functional analysis. Issue 2 (February 2020) - Lo Torto, Federico; Kaciulyte, Juste; Marcasciano, Marco; Casella, Donato; Bernetti, Andrea; Mangone, Massimiliano; Agostini, Francesco; Ciudad, Pedro; Fioramonti, Paolo; Ruggiero, Marco; Ribuffo, Diego; Carlesimo, Bruno
Highlights: Surgical repair is the first treatment in Achilles tendon ruptures, but it has significant risk of complications. In complicated Achilles tendon re-ruptures with fringed stumsps, Peroneus Brevis flap is a valid reconstructive technique. Peroneus Brevis flap presents the benefits of autologous free tissues flaps, with less risk of failure. Abstract: Background: We would like to describe our experience with Peroneus Brevis flap in complicated Achilles tendon re-ruptures with fringed stumps. Methods: Eight patients with monolateral re-rupture of Achilles tendon were selected as eligible for surgical repair with Peroneus Brevis flap. Patients' outcome was evaluated clinically (ATRS and ROM), functionally (Gait analysis) and MRI was performed before and after surgery. Results: Effective coverage of tissue defect was reached in all patients. Functional assessment evaluation results were registered in a follow-up time that ranged from 12 to 18 months. ATRS and ROM tests' results showed good functional recovery without functional limitations or subjective reports pain. Post-operative MRI showed no signs of inflammation or tissue gaps. Gait analysis showed a partial reduction of performance in the affected side that did not affect patients' quality of life. Conclusions: In the presence of fringed stumps in Achilles tendon re-rupture, tendon flaps have the benefits of autologous tissues transfers and present less risks of failure than free flaps. Among them, Peroneus Brevis flap is easy to perform and leads to donor site's low morbidity. Our preliminary experience provides support for this technique to be potentially validated in larger more controlled trial.